Visual analysis of humans looking at people - Moeslund, Thomas; SpringerLink (Online service). (London New York Springer, 2011)
Understanding human activity from video is one of the central problems in the field of computer vision, driven by a wide variety of applications in communications, entertainment, security, commerce, and athletics. This unique text/reference provides a coherent and comprehensive overview of all aspects of video analysis of humans. Broad in coverage and accessible in style, the text presents original perspectives collected from preeminent researchers gathered from across the world. In addition to presenting state-of-the-art research, the book reviews the historical origins of the different existing methods, and predicts future trends and challenges. Topics and features: With a Foreword by Professor Larry Davis of the University of Maryland Institute for Advanced Computer Studies, USA Contains contributions from an international selection of leading authorities in the field Includes an extensive glossary Discusses the problems associated with detecting and tracking people through camera networks Examines topics related to determining the time-varying 3D pose of a person from video Investigates the representation and recognition of human actions Reviews the most important applications of activity recognition, from biometrics and surveillance, to sports and driver assistance With its all-encompassing scope, this essential reference will be of great value not only to graduate students in computer vision, but also to all researchers and professionals interested in systems for the visual analysis of humans. Dr. Thomas B. Moeslund is an Associate Professor in the Department of Architecture, Design &  Media Technology at Aalborg University, Denmark. Dr. Adrian Hilton is Professor and Head of the Visual Media Research Group at the University of Surrey, Guildford, UK. Dr. Volker Krüger is an Associate Professor and Head of the Computer Vision and Machine Intelligence Laboratory at Aalborg University. Dr. Leonid Sigal is a Research Scientist at Disney Research, Pittsburgh, PA US
Part I: Detection and Tracking -- Is There Anybody Out There?- Beyond the Static Camera: Issues and Trends in Active Vision -- Figure-Ground Segmentation: Pixel-Based: Figure-Ground Segmentation: Object Based -- Face Detection -- Wide Area Tracking in Single and Multiple Views -- Benchmark Datasets for Detection and Tracking -- Part II: Pose Estimation -- Articulated Pose Estimation and Tracking: Introduction -- Model-based Pose Estimation -- Motion Models for People Tracking -- Part-based Models for Finding People and Estimating Their Pose -- Feature-based Pose Estimation -- Benchmark Datasets for Pose Estimation and Tracking -- Part III: Recognition -- On Human Action -- Motion Pattern Analysis for Modeling and Recognition of Complex Human Activities -- Action Recognition Using Topic Models.Learning Action Primitives -- Contextual Action Recognition -- Facial Expression Analysis -- Part IV: Applications -- Applications for Visual Analysis of People -- Image and Video-based Biometrics -- Security and Surveillance -- Predicting Pedestrian Trajectories -- Human Computer Interaction -- Social Signal Processing: The Research Agenda -- Sign Language Recognition -- Sports TV Applications of Computer Vision -- Multi-view 4D Reconstruction of Human Action for Entertainment -- Vision for Driver Assistance: Looking at People in a Vehicle.
Electronic reproduction.
Keywords: Human face recognition (Computer science); Electronic books